2004
DOI: 10.1007/s10350-003-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes After Total Mesorectal Excision for Cure for Cancer of the Lower Rectum: Anterior vs. Abdominoperineal Resection

Abstract: T4 tumors, R1 resections, and/or intraoperative perforation of the tumor or bowel wall are main features of low rectal cancers, causing inferior oncologic outcomes for tumors in this area. If surgery is optimized, preventing intraoperative perforation and involvement of the circumferential resection margin, the prognosis for cancers of the lower rectum seems not to be inherently different from that for tumors at higher levels. In that case, the level of the tumor or the type of resection will not be indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
233
4
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(269 citation statements)
references
References 33 publications
24
233
4
8
Order By: Relevance
“…The rise in the number of ELAPE procedures performed reflects surgeons' preferences for the procedure, supported by the lower rates of local recurrence and improved survival reported by previous studies. 3,6,8 Our study did not demonstrate any oncological superiority for either of the two procedures in terms of disease free survival or long-term survival. Furthermore, there was no significant difference in overall long-term QoL between patients who had ELAPE and those who had SAPE, which is consistent with previous findings on short-term outcomes.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The rise in the number of ELAPE procedures performed reflects surgeons' preferences for the procedure, supported by the lower rates of local recurrence and improved survival reported by previous studies. 3,6,8 Our study did not demonstrate any oncological superiority for either of the two procedures in terms of disease free survival or long-term survival. Furthermore, there was no significant difference in overall long-term QoL between patients who had ELAPE and those who had SAPE, which is consistent with previous findings on short-term outcomes.…”
Section: Discussioncontrasting
confidence: 53%
“…2 Abdominoperineal excisions are performed for cancers within 6cm of the anal verge. 2,3 Compared with anterior resection, standard abdominoperineal excision (SAPE) is more invasive, and has higher rates of local recurrence, morbidity and mortality. 2,4,5 Over the last decade, attempts have been made to modify SAPE to reduce the rate of local recurrence and improve survival.…”
mentioning
confidence: 99%
“…Lymph node metastases (LNM) of adenocarcinoma of the colon and rectum have been established as an independent prognostic factor [2]. Therefore, the radical resection of the local lymphdraining tissue led to a significant improvement of oncological results by lowering the local recurrence rate [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Although neoadjuvant treatment significantly down staged tumors on final histopathology, significant portion of our patients had pT3/T4 tumors and pN2 nodal disease. It has been shown before that locally advanced pT4 tumors and pathological nodal positivity adversely impact CRM status (Wibe et al, 2004;Kenelly et al, 2013). We generally operate patients within 6-8 weeks of chemoradiation but due to tremendous workload, this was not always possible.…”
Section: Discussionmentioning
confidence: 97%
“…CRM positivity as high as 26% has been reported in patients with low rectal cancers who undergo APR (Nagtegaal et al, 2002;Bernstein et al, 2009). In modern practice, suggested target value of a positive CRM is close to 10% (Nagtegaal et al, 2002;Wibe et al, 2004). A recent study from Malaysia reported a CRM positive rate of 18.4% after long course chemoradiation and surgery (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%